Comparative analysis of social media accessibility - Bocheński, Bartosz (Journal of Computer Sciences Institute, 2023)
The paper assesses the accessibility compliance level of social media websites and their usability in terms of universal design. The study was performed on “reddit” and a social media website created by the author of the article for the express purpose of meeting the WCAG requirements as closely as possible, named “Twittn’t”. The analysis has been performed with the use of a survey study, an automated WAVE tool and an eye-tracker. The research groups consisted of fifteen and twenty people for survey and eye-tracker study respectively. The test results have shown strong correlation between usability of the social media website interface and number of its WCAG errors.